Microbiological characterisation of the colonisation by Candida sp in patients with orthodontic fixed appliances and evaluation of host responses in saliva. Issue 3 (15th January 2019) - Tapia, Cecilia V.; Batarce, Christian; Amaro, José; Hermosilla, German; Rodas, Paula I.; Magne, Fabien
Abstract: Objectives: We investigated the colonisation by Candida spp in patients using orthodontic fixed appliances by characterising the isolated Candida strains and by evaluating the host oral mucosa response through the measure of human β‐defensins 3 (HBD‐3) expression and Interleukin‐1ß/IL‐10. Methods: Ninety patients were enrolled after signing an informed consent. Prevalence, susceptibility to fluconazole, genotyping and oral fungal burden of Candida sp. isolated were determined. Host responses were evaluated by measuring HBD‐3 expression as well as IL‐1ß and IL‐10 in saliva. Results: The colonisation rate reached 6.7% (6/90), and 5 patients were colonised with C. albicans strains and one with one with C. tropicalis . The fluconazole MIC90/susceptibility of C. albicans strains ranged 1/0.25‐1 μg/mL. However, isolated strains did not present different genotype (SAB>0.9), C. albicans colonisation seems to be influenced by the duration of treatment and by level expression of HBD3 that were higher in colonised patients (not statistically different). A negative correlation between the fungal burden and IL‐1ß levels was found in colonised patients but not for IL‐10. Conclusions: Our study revealed that patients with orthodontic fixed appliances were mainly colonised by C. albicans, which was related to a decrease in HBD‐3 expression and IL‐1ß levels.